2011
DOI: 10.1093/brain/awq360
|View full text |Cite
|
Sign up to set email alerts
|

In vivo monitoring of neuronal loss in traumatic brain injury: a microdialysis study

Abstract: Traumatic brain injury causes diffuse axonal injury and loss of cortical neurons. These features are well recognized histologically, but their in vivo monitoring remains challenging. In vivo cortical microdialysis samples the extracellular fluid adjacent to neurons and axons. Here, we describe a novel neuronal proteolytic pathway and demonstrate the exclusive neuro-axonal expression of Pavlov’s enterokinase. Enterokinase is membrane bound and cleaves the neurofilament heavy chain at positions 476 and 986. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 72 publications
4
48
0
Order By: Relevance
“…Increased apoptosis in MBP and NF damage the white matter of CNS (Petzold et al, 2011;Pun et al, 2011). In consistence, we find that the impairment in postnatal oligodendrocytes and axons further increased cellular apoptosis in the brain and O.N.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased apoptosis in MBP and NF damage the white matter of CNS (Petzold et al, 2011;Pun et al, 2011). In consistence, we find that the impairment in postnatal oligodendrocytes and axons further increased cellular apoptosis in the brain and O.N.…”
Section: Discussionmentioning
confidence: 99%
“…extension (Chow et al, 2009). An enhanced apoptosis reduces the white matter content in CNS (Petzold et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, biomarkers released by cortical pathology are likely to be found quicker and at higher concentration in the bloodstream due to diffusion through the cortical arachnoid villi [22]. Potential factors influencing NfH release include systemic blood pressure, haemodilution and brain temperature [26]. Glucose metabolism and glutamate toxicity are additional factors which could influence NfH release in the setting of cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate: pyruvate ratios reflect anaerobic glycolysis secondary to ischemia and mitochondrial failure with ratios >20-25 being associated with poor outcome in TBI [36][37][38]. Glycerol levels of >100 μmol/L, glucose levels <1.5-2 mmol/L, and glutamate levels >15-20 mol/L are also associated with poor outcome and reflect metabolic crisis in TBI [39]. This technique has allowed the exploration of other biomarkers such as neurofilament heavy chain which, in one study, had an OR 7.68 for predicting mortality in TBI which was superior to ICP, GCS, and CPP [40•] and Tau levels which, in another preliminary study, were found to correlate with MRI DTI and may be a possible marker for traumatic axonal injury [41•].…”
Section: Microdialysismentioning
confidence: 99%